2023
DOI: 10.1177/13524585231159817
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological MEG markers of cognitive impairment and performance validity in multiple sclerosis

Abstract: Background: Suboptimal performance during neuropsychological testing frequently occurs in multiple sclerosis (MS), leading to unreliable cognitive outcomes. Neurophysiological alterations correlate with MS-related cognitive impairment, but studies have not yet considered performance validity. Objectives: To investigate neurophysiological markers of cognitive impairment in MS, while explicitly addressing performance validity. Methods: Magnetoencephalography recordings, neuropsychological assessments, and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While the exact mechanisms underlying cognitive dysfunction in MS remain incompletely understood, evidence suggests a potential link between synaptic loss, particularly in inhibitory synapses, and cognitive impairment. 2 Previous in vivo studies in MS 5,6 using magnetoencephalography/electroencephalography (MEG/EEG) have primarily focused on investigating the relationship between oscillatory biomarkers and cognitive performance during resting state and while performing a task. Nevertheless, it has also been shown that the non-oscillatory component of neuronal activity contains functionally relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…While the exact mechanisms underlying cognitive dysfunction in MS remain incompletely understood, evidence suggests a potential link between synaptic loss, particularly in inhibitory synapses, and cognitive impairment. 2 Previous in vivo studies in MS 5,6 using magnetoencephalography/electroencephalography (MEG/EEG) have primarily focused on investigating the relationship between oscillatory biomarkers and cognitive performance during resting state and while performing a task. Nevertheless, it has also been shown that the non-oscillatory component of neuronal activity contains functionally relevant information.…”
Section: Introductionmentioning
confidence: 99%